Self Representasion of Adolescence on Instagram Social Media - Hendy Harnio Pratama (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
ABSTRACTA teenagers in this century are very familiar and capable to adapt by using social media being part of their daily activities, especially teenagers in Lhokseumawe City. This research is to explain how teenagers in representated their self on Instagram as a social media. The purpose of this research is to see how a teenager managing their self impression through self representation using photo or video that have been uploaded to their Instagram account, also want to see are the teenagers capable to differentiate between real life and virtual life. Approaching this research is using a qualitative descriptive with case study as the type of research. The procedure by taking a sample using purposive sampling technique, and collecting the data by interview and documentation. Then, the data been analyze using data analysis technique in the form of reduction data, scheme of representment of data and conclusion. In this research, the theory using The Dramaturgi of Erving Goffman. The result of this research showing that the teenagers in Lhokseumawe City using a social media of Instagram as self representation by showing their self impression differently. It happens because the teenagers has different ways of necessity and purpose in showing their self impression to make their followers on Instagram account attractive by their post. The kind of impressions on this research showed up such as the teenagers actively on internal and external organizations, food hobbies, love travelling and the others. In generally, a teenagers capable by using social media Instagram in good ways, because their knowing that the Instagram is just a stage for showing their good looking, expressions by many of the purpose that their prepared for the Instagram account.Keywords: Self representation, Instagram, Self Impressions.